SISTEM KONTROL SUHU DENGAN PID DAN MONITORING DAYA OUTPUT PADA PANEL PHOTOVOLTAIC PORTABLE DENGAN VIRTUAL PRIVATE SERVER - Ardian Nurrahman; Nazori AZ (MAESTRO, 2020)
Photovoltaic (PV) is a system capable of converting sunlight into electrical energy. In this modern era, the photovoltaic system has produced many benefits, such as emergency energy when the main energy is not available, to be able to monitor the output of the photovoltaic system can be done in various ways, from storing data loggers on SD cards, to using remote systems. such as IoT (Internet Of Things). The design system of this tool consists of a 30 Wp photovoltaic, temperature sensor, current sensor, voltage sensor, lux sensor, atmega 2560, Peltier, 12 V battery, raspberry Pi, VPS. The system works by controlling the temperature with the PID method to reduce heat that affects photovoltaic performance and the photovoltaic monitoring system to find out how much usage has been used with a virtual private server, which is expected to be used as a portable tool that can help when natural disasters occur, so that it can be monitored. and controlled from anywhere. From the tests carried out with the input setpoint 27,28,29,30,31, it was found that the average PID output in the form of PWM for each setpoint was 205.65, 226.74,232.53,174.97,204.